Zdravljenje spastičnosti z intratekalnim baklofenom - Grabljevec, Klemen (Rehabilitacija (Ljubljana), 2009)
In some patients, severe spasticity of cerebral or spinal origin cannot be treated succesfully with conventional oral medication or physical modalities. Intrathecal baclofen therapy with implanted pump represents an effective treatment since mid 80's. Baclofen (Lioresal) is a muscle relaxant and potent GABA agonist that acts via GABAb receptors at the posterior coloumns of spinal cord level to inhibit the release of excitatory neurotransmiters by inhibiting calcium ions influx into presynaptic terminals. This direct binding on spinal cord receptors leads to higher efficiency compared to peroral therapy in which baclofen does not pass the brain-blood barrier. In Slovenia, there are presently 34 patients having intrathecal pump implanted, three of those receiving morphium sulfate as an intractable pain therapy. In this article, we describe indications and contraindications for intrathecal baclofen therapy, selection and preparation of patients for surgery, the surgical procedure of pump implantation, long term follow-up with pump refill procedure and possible complications of intrathecal baclofen therapy. We also present our experiences from the Centre for Spasticity Treatment at the University Rehabilitation Institute in Ljubljana.
Keywords: spastičnost; neurology; nevrologija; intratekalni baklofen; therapy; zdravljenje; baklofenska črpalka; rehabilitacija; vocational rehabilitation